Determination of ph of platelet concentrates and its relations with febrile non-hemolytic transfusion reactions - Rosline, Hassan (Pusat Pengajian Sains Perubatan, 2013)
Platelet transfusion is associated with numerous adverse reactions and the most common one is febrile non-haemolytic transfusion reaction (FNHTR). Although it is not a life threatening condition, the clinical symptoms could lead to discomfort to the patients as well as utilizing the nursing and laboratory resources. Platelet concentrates are stored at 22•c which can lead to increased lactate production as a result of glycolysis and falling in pH. Moreover the presence of leucocytes and bacterial contamination in the platelets concentrate lead to a competition for the availability of oxygen which too, will result in a rapid fall in the pH. This study was done to determine the relationship between pH of the platelet concentrates and febrile non haemolytic transfusion reaction ( FNHTR) and to correlate the pH with the white blood cell & platelet count presence in the platelet concentrates. Hundred and fifty samples of platelet concentrates were included in this study . Only 4 episodes of febrile reactions were detected in I 04 episodes of transfusion. The pH of the platelet concentrates was reduced throughout the day but was still maintained within the guideline recommendations. There was a significant correlation between pH and platelet count but not with the WBC count. There was no bacterial contamination detected in all the units studied. As a conclusion, the incidence of FNHTR is low among patients receiving platelet transfusion in this study and did not appear to be associated with pH. Based on the mean pH value of the platelet concentrates were well maintained within the usual 5 days, thus an extension of platelet storage time is recommended.